Ethnopharmacology of wild plants - Rai, Mahendra; Bhattarai, Shandesh, 1977-; Feitosa, Chistiane Mendes (Boca Raton : CRC Press, 2021)
The book provides valuable information on wild plants and their ethnopharmacological properties, discussion on ethnobotany, phytotherapy, diversity, chemical and pharmacological properties including antifungal, anti-inflammatory and antiprotozal properties. The chapters include a wide range of case studies, giving updated evidence on importance of wild plant resources from different countries including Nepal, India, Brazil, Chile, Argentina, Colombia, Egypt, Peru, etc. In addition, some specific species are used to explain their potential properties. Discussing traditional usage and pharmacological properties of wild plants, this book is entirely different from other related publications and useful for the researchers working in the areas of conservation biology, botany, ethnobiology, ethnopharmacology, policy making, etc.
OCLC-licensed vendor bibliographic record.
Keywords: Medicinal plants; Ethnopharmacology; Materia medica, Vegetable; Wild plants, Edible -- Therapeutic use; HEALTH & FITNESS / Herbal Medications; MEDICAL / Alternative Medicine; SCIENCE / Life Sciences / Botany